Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Routine Complete Blood Count Components in HELLP Syndrome: A Matched Case Control Study - Giovanni Sisti; Andrea Faraci; Jessica Silva; Ruchi Upadhyay (Medicina, 2019)
Background and objective: Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are new readily available inflammatory markers that have been analyzed in pregnancy-induced hypertensive disorders such as preeclampsia. Studies on the NLR/PLR ratio in hemolysis, elevated liver enzymes, low-platelet count (HELLP) syndrome are limited in the current literature. We compared NLR/PLR and other complete blood count (CBC) components between women with HELLP syndrome and women with healthy pregnancies. Methods: We conducted a retrospective matched case–control study at a tertiary care hospital in NY (USA) in the time frame between January 2016 and December 2018. The study compared pregnant women with HELLP syndrome (cases) to women with healthy pregnancies in the third trimester (controls), matched by age, body mass index (BMI), parity, and race. Patient with preeclampsia, infection, and fever were excluded. Venous blood samples were obtained as part of the routine work-up at admission for delivery, which included a CBC. The main outcomes were NLR and PLR. The secondary outcomes were hemoglobin, red cell distribution width (RDW), platelet count, mean platelet volume (MPV), neutrophils, lymphocytes. Results: There were 14 patients in each group. They were matched by age, race, BMI, and parity. NLR (5.8 vs. 3.6, p-value = 0.002) and neutrophil count (10.7 vs. 6.8, p-value = 0.001) were higher in women with HELLP compared to controls. PLR (34 vs. 130.2, p-value < 0.001) and platelet count (71 vs. 223, p-value < 0.001) were lower in the study group compared to controls. Conclusions: NLR was higher, and PLR was lower in women with HELLP syndrome. These inflammatory markers can be incorporated into the diagnostic algorithm for HELLP syndrome. Future studies are needed to evaluate their ability to predict HELLP syndrome.